2005
DOI: 10.1002/j.1556-6678.2005.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Child-Centered Group Play Therapy With African American Boys at the Elementary School Level

Abstract: Culturally sensitive counseling interventions are needed for African American boys in elementary school. Two important components of counseling African American boys are honoring the African worldview and building self‐confidence. Child‐centered group play therapy is a common intervention for elementary school children. In this article, the authors describe how child‐centered group play therapy with African American boys at the elementary school level honors the African worldview and facilitates their self‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…The results of this study showed the effect of child-centered play therapy on the preoperative developmental stages and objective operations of children in the experimental group. Play therapy has a positive effect on behavior and emotions, and can act as counseling for children and treatment for adults [17].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed the effect of child-centered play therapy on the preoperative developmental stages and objective operations of children in the experimental group. Play therapy has a positive effect on behavior and emotions, and can act as counseling for children and treatment for adults [17].…”
Section: Discussionmentioning
confidence: 99%
“…The results also reported that CCPT was more effective in comparison to directive approaches (Bratton et al, 2005). A growing body of research supports the effectiveness of play therapy with minority children (Baggerly & Parker, 2005; Garza & Bratton, 2005; Shen, 2002). However, no studies have measured the effectiveness of CCPT with Muslim children in Western countries.…”
Section: Ccptmentioning
confidence: 99%
“…These messages convey to them that they do not belong and that they are not capable of succeeding in academics. As a result, Black boys are socialized in early education to lack self‐confidence and a sense of belonging in school (Baggerly & Max, ). This circumstance is further influenced by the lack of diversity among preK–12 teachers.…”
Section: Contextualizing the Experiences Of Black Men In Society And mentioning
confidence: 99%